Drawing as an Expressive Activity: The Theoretical Foundation and Application in Psychology - Zarhbouch, Benaissa; Lamkaddem, Abdelaziz; Souirti, Zouhayr (LANGUAGE ART, 2020)
Through this article, we will address the activity of drawing as an expressive activity that refers to the emotional, cognitive and kinetic dimensions, through the presentation of the most important theories that were performed by the pioneers, which marked the beginning of new perceptions that went beyond the classical view that is a universal activity. Besides, we target to highlight that drawing is governed by cultural and neurological constraints, as well as by other variables such as age and sex. The most important conclusions are: the expression by painting is governed by universal requirements, influenced by cultural peculiarities, as well as age and gender variables. Hence, its adoption in clinical or educational practice must be very careful and based on drawing studies according to the cultural context.